The Australian Metropolis 2000-2015 - Hamnett, Stephen; Freestone, Robert (International Planning History Society Proceedings, 2016)
In 2000 the authors published The Australian Metropolis: A Planning History, an account of the evolution of Australian metropolitan planning from the early years of colonial settlement to the end of the twentieth century. Most state governments were by then pursuing strategies to make their capital city-regions more compact and were encouraging reduction in car dependency. The final chapter identified a growing tension between ‘sustainable’ and ‘productive’ aspirations. On the one hand, environmental concerns were seen as underpinning renewed popular and political support for public planning. On the other was the rise of what we called ‘market triumphalism’, acknowledging the turn to neo-liberal policies preoccupied with global competitiveness alongside evidence of growing inequality, social diversity and ‘short-termism’ of political priorities. This paper looks at what has happened to Australian metropolitan planning in the decade and a half since the book was published. The opening decade of the twenty-first century saw sustained economic growth, largely as a consequence of a resource boom triggered by rising levels of industrial activity and consumption amongst Australia’s largest trading partners, albeit slowed for several years by the Global Financial Crisis. Australia’s population continues to expand and the current total of around 24 million is likely to double in the present century. Growth is concentrated in the larger capital cities with some recurring trends and challenges including the decline of suburban manufacturing employment and growth of new ‘knowledge economy’ jobs mainly in the inner cities; housing unaffordability, especially in the two largest cities of Sydney and Melbourne; the continued shift to higher density and high rise urban forms through urban renewal; growing infrastructure deficits, particularly in public transport; a growing gulf in access to services and quality of life; and dysfunctionalities in metropolitan governance. Against this background, the paper overviews the planning strategies prepared for the five mainland state capitals of Sydney, Melbourne, Brisbane, Adelaide and Perth over the period 2000-2015. Drawing on a survey of primary documents and a growing body of research, the treatment highlights major planning trends, similarities and differences between the major cities. Major themes have included further promotion of anti-sprawl policies of infill and redevelopment; transit-oriented development; privatisation of public infrastructure such as motorways and airports; dealing with the spatial mismatch between homes and jobs; a resurgence of urban design; and growing administrative fragmentation. State governments have deployed their executive power to drive through major redevelopment projects, with a corresponding reduction in public participation, and they are under continuing pressure to reform planning systems in order to facilitate economic growth with mixed success. The national government has latterly become re-engaged in urban development primarily as the crucial links between urban investment, infrastructure, GDP and planning systems become more evident. The paper ends by reflecting on an evolving style of Australian metropolitan planning in the early twenty first century in pursuit of an increasingly complex and often competing set of aspirations for productive, sustainable, liveable and well-governed cities.